1976
DOI: 10.1128/jb.127.1.91-97.1976
|View full text |Cite
|
Sign up to set email alerts
|

Natural and altered induction of the L-fucose catabolic enzymes in Klebsiella aerogenes

Abstract: Mutants of Klebsiella aerogenes W70 were isolated that had gained the ability to utilize the uncommon pentose D-arabinose as their sole source of carbon and energy. In contrast to the D-arabinose-negative, parent strain, these mutants were found to be either constitutive for certain enzymes of the L-fucose catabolic pathway or inducible for such enzymes when incubated in the presence of D-arabinose. The mutants used L-fucose isomerase to convert D-arabinose to D-ribulose, which is an intermediate and inducer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Further, we hypothesized that adaptation routinely begins with the overexpression of ambiguous and/or promiscuous enzymes. Anecdotal evidence in support of this hypothesis includes early experiments showing that the enzymes of fucose metabolism could be recruited for the catabolism of L-1,2propanediol (Cocks et al 1974) and D-arabinose (St Martin and Mortlock 1976). Campbell, Hall, and Hartl also demonstrated that a repressor mutation enabling constitutive expression of a cryptic β-galactosidase, Ebg, was critical for its ability to suppress E. coli lacZ mutants (Hall 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we hypothesized that adaptation routinely begins with the overexpression of ambiguous and/or promiscuous enzymes. Anecdotal evidence in support of this hypothesis includes early experiments showing that the enzymes of fucose metabolism could be recruited for the catabolism of L-1,2propanediol (Cocks et al 1974) and D-arabinose (St Martin and Mortlock 1976). Campbell, Hall, and Hartl also demonstrated that a repressor mutation enabling constitutive expression of a cryptic β-galactosidase, Ebg, was critical for its ability to suppress E. coli lacZ mutants (Hall 2003).…”
Section: Introductionmentioning
confidence: 99%